Integration of E-LKPD Liveworksheet-Assisted Problem-Based Learning Model into Critical Thinking Skills of Science Subjects - Siti Halimatus Sakdiyah; Yuli Ifana Sari; Ravinesh Rohit Prasad (International Journal of Social Learning (IJSL), 2026)
This study analyzes the influence of the Problem-Based Learning (PBL) model assisted by e-LKPD Liveworksheet on the critical thinking skills of fifth-grade students in Natural and Social Sciences (IPAS) subjects at the elementary school level. Strengthening critical thinking is essential in supporting 21st-century learning, which requires students to analyze information, evaluate ideas, and solve problems independently. This research employed a quasi-experimental Pretest–Posttest Nonequivalent Control Group Design with 58 students, divided into an experimental and a control group. Critical thinking skills were measured using a validated and reliable ten-item multiple-choice test. Data were analyzed for normality and homogeneity, and an independent t-test and N-Gain calculations were performed using SPSS version 22. The findings indicate that the PBL model supported by e-LKPD Liveworksheet significantly improved students’ critical thinking skills, evidenced by a significance value of 0.000 (< 0.05) and an average N-Gain score of 0.6179 in the medium-high category. These results demonstrate that integrating PBL with digital worksheets encourages active, contextual, and technology-enhanced learning. The study concludes that e-LKPD–assisted PBL is an effective and innovative strategy for enhancing elementary students’ critical thinking skills.